Mapping tooth number anomalies: a radiographic cross-sectional study in pediatric dentistry - Maria Inês Guimarães; Isabel Abreu; Beatriz Carneiro; Teresa Sequeira; Augusta Silveira; Cristina Cardoso Silva (Revista Portuguesa de Estomatologia, Medicina Dentária e Cirurgia Maxilofacial)
Objectives: Understanding the prevalence of dental anomalies is crucial for improving diagnosis and treatment by dentists. Additionally, documenting these anomalies is vital in Legal Medicine, where dental records are instrumental in forensic investigations. Tooth number anomalies, such as agenesis and supernumerary teeth, significantly impact a child's oral health and development. This study aimed to determine the prevalence of tooth number anomalies in a pediatric population and highlight the significance of detecting and documenting such anomalies. Methods: Tooth number anomalies were identified in a pediatric population (6–18 years old) attending the Pedagogical Dental Clinics of the Faculty of Health Sciences of Fernando Pessoa University, through panoramic radiographs. Statistical analysis was conducted using IBM© SPSS© Statistics version 25.0. Results: Analysis of 147 panoramic radiographs revealed that 10.8% exhibited tooth number anomalies, with 8.8% presenting agenesis and 2.0% supernumerary teeth. The mandibular second premolar was the most frequently affected by agenesis, followed by the maxillary second premolar. Three cases of supernumerary teeth were identified: two in the maxilla and one in the mandible, all within the midline area. Conclusions: Agenesis was the most prevalent tooth number anomaly in this study. No significant correlation was found between sex and tooth number anomalies identified. Though infrequent, detecting and documenting these anomalies hold immense significance within the patient's clinical history, serving as a crucial asset for future identification endeavors.